Meneroka Pemikiran Ibn Taymiyah: Kritik Terhadap Filsafat dan Tasawuf - Usman, Muh Ilham (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2020)
This paper presents the results of the thought of Ibn Taymiyya who criticized philosophy and Sufism. This study uses the thought of character that reveal ideas that have been born by a Muslim scholar. By using a historical approach that sees the Moslem scholars as a historical person who takes part in social reality. The results of the study found that Ibn Taymiyya criticized philosophy in term of Aristotelian logic which had been widely used by Muslim scholars at the time. Whereas in Sufism, Ibn Taymiyya was not entirely Sufis, only he made his criticism of the philosophical Sufism figures and the tarekat practitioners who developed in his day.Tulisan ini menyajikan hasil pemikiran Ibn Taymiyyah yang melakukan kritik terhadap filsafat dan tasawu. Penelitian ini menggunakan pemikiran kajian tokoh yakni mengungkap gagasan dan ide yang pernah dilahiran oleh seorang tokoh. Dengan menggunakan pendekatan historis yakni melihat sang tokoh sebagai manusia sejarah yang berkiprah dalam realitas sosial. Hasil kajian menemukan bahwa Ibn Taymiyah tidak sepenuhnya anti-tasawuf, malahan ia sangat mengapresiasi beberapa sufi awal, hanya saja ia melancarkan kritiknya terhadap para tokoh tasawuf falsafi dan para pengamal tarekat yang berkembangn pada zamannya.